Duodenal Stump Therapy Treatable with Duodenal Round Ligament of Liver - I. I. Taranov; V. A. Bondarenko; E. A. Atroshenko; A. A. Kolesnichenko (Медицинский вестник Юга России, 2012)
Purpose: Show the ability to handle the stump of the duodenum using the entire thickness of the round ligament of liverMaterials and Methods: For treatment of the stump of the duodenum during surgery for gastric resection with Billroth II penetrating into the head of the pancreas or liver gates ulcers developed a method of providing for the imposition of two rows of stitches with the capture of the second series of the entire thickness of the roundligament of liver.Results: In this method, carried out processing of the stump of the duodenum in 12 patients with penetrating into the head of the pancreas or liver gates duodenalulcersSummary: When performing gastrectomy Billroth II on penetrating into the head of the pancreas or liver gates ulcers can process duodenal stump using he entire thickness of the round ligament of liver